DESIGN AND IMPLEMENTATION OF TELEGRAM BOT FOR INTEGRATED HOSPITAL INFORMATION SYSTEM - Sudana, Oka; Paramartha, Ary; Wirdiani, Ayu; Rusjayanthi, Dwi (JST (Jurnal Sains dan Teknologi), 2022)
Hospitals with the work complexity level in it require an information system to help solve their problems. Each part of the hospital requires a different module. The module needs to integrate so that the data exchange flow becomes easier. The use of internet messengers, such as Telegram, can simplify the integration process required, thereby users can easily get information from the system. This article explained how to design bots on the Telegram platform to help users acquire information from the system easily. This Telegram Bot used the help of Cronjobs and Webhooks to retrieve information and execute messaging commands for the Telegram Bot. The results shown in this research were Telegram Bots designed to be tested using the User Acceptance Test (UAT) with very positive response results and are considered successful